Memahami Makna Tujuan Utama Manusia: Sebuah Refleksi Katekismus Singkat Westminster [Understanding the Meaning of The Chief End of Man: A Reflection of the Westminster Shorter Catechism] - Musa Sinar Tarigan (Diligentia: Journal of Theology and Christian Education, 2022)
The chief end of man is to glorify God and enjoy Him throughout his life according to Westminster Shorter Catechism. Glorifying God and enjoying Him means that humans acknowledge the existence of God and apply God's truth in all aspects of their lives according to the Word of God. Enjoying and glorifying God is a privilege given by God to Christians who are created in the image and likeness of God. As a result of the fall of man into sin, and sinful humans cannot know God properly according to the Word of God. The redemption of Christ on the cross reconciles believers with God, and they can relate with God even though they also have to struggle against sin. The method of writing this article uses literature research to examine the issue of the spiritual growth of believers, through various theological literature, both relevant books and journals, and the Bible as the main source. The writing of this article aims to understand the purpose of human life which is to glorify and enjoy God throughout life, and its application in daily life, recognizing the various traps of false spiritual growth. Glorifying God and enjoying Him could only be experienced when believers experience Christ's redemption and grow more Christlike in absolute obedience to Christ.BAHASA INDONESIA ABSTRACT: Tujuan utama manusia adalah untuk memuliakan Allah dan menikmati Dia sepanjang hidupnya menurut Katekismus Singkat Westminster. Memuliakan Tuhan dan menikmati Dia berarti manusia mengakui keberadaan Tuhan dan menerapkan kebenaran Tuhan dalam seluruh aspek kehidupannya sesuai dengan Firman Tuhan. Menikmati dan memuliakan Allah adalah hak istimewa yang diberikan Allah kepada orang Kristen yang diciptakan menurut gambar dan rupa Allah. Akibat kejatuhan manusia ke dalam dosa, manusia yang berdosa tidak dapat mengenal Allah dengan benar sesuai dengan Firman Tuhan. Penebusan Kristus di kayu salib memperdamaikan orang percaya dengan Allah, dan mereka dapat berhubungan dengan Allah walaupun mereka juga harus bergumul melawan dosa. Metode penulisan artikel ini menggunakan penelitian kepustakaan untuk menelaah masalah pertumbuhan rohani orang percaya, melalui berbagai literatur teologi, baik buku-buku maupun jurnal yang relevan, dan Alkitab sebagai sumber utama. Penulisan artikel ini bertujuan untuk memahami tujuan hidup manusia yaitu memuliakan dan menikmati Tuhan sepanjang hidup, serta penerapannya dalam kehidupan sehari-hari, dengan mengenali berbagai jebakan pertumbuhan rohani yang palsu. Memuliakan Tuhan dan menikmati Dia hanya dapat dialami ketika orang percaya mengalami penebusan Kristus dan bertumbuh menjadi semakin serupa dengan Kristus dalam ketaatan yang mutlak kepada Kristus.